2015
DOI: 10.1371/journal.pone.0136726
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization (FISH) Assays for Diagnosing Malaria in Endemic Areas

Abstract: Malaria is a responsible for approximately 600 thousand deaths worldwide every year. Appropriate and timely treatment of malaria can prevent deaths but is dependent on accurate and rapid diagnosis of the infection. Currently, microscopic examination of the Giemsa stained blood smears is the method of choice for diagnosing malaria. Although it has limited sensitivity and specificity in field conditions, it still remains the gold standard for the diagnosis of malaria. Here, we report the development of a fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
62
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 20 publications
0
62
1
Order By: Relevance
“…Despite the fact that PCR was used, which is a more sensitive method for evaluating diagnostic performance, the sensitivity of the FISH assay was poor in this study as compared to a previous study by Shah et al which showed that the sensitivity of the P-Genus FISH assay was 98% when compared to Giemsa microscopy [7]. The specificity of P-Genus FISH in the current study was 75.8% which is closely similar to the previous study (83.4%) by Shah et al although she compared her study with Giemsa microscopy.…”
Section: Discussioncontrasting
confidence: 58%
“…Despite the fact that PCR was used, which is a more sensitive method for evaluating diagnostic performance, the sensitivity of the FISH assay was poor in this study as compared to a previous study by Shah et al which showed that the sensitivity of the P-Genus FISH assay was 98% when compared to Giemsa microscopy [7]. The specificity of P-Genus FISH in the current study was 75.8% which is closely similar to the previous study (83.4%) by Shah et al although she compared her study with Giemsa microscopy.…”
Section: Discussioncontrasting
confidence: 58%
“…While we used nucleic acid stains for sensitive detection of P. falciparum parasites in thin blood smear, different probes that are specific to a set of pathogens can also be utilized. The past decades has seen much development of pathogen specific probes [75, 76, 77, 78]. Being low-cost and highly configurable, Octopi has the potential to help realize the wide spread use of these new probes in field diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of FISH assays for malaria compared to the more sensitive nested PCR assays have been previously discussed in detail for the P. falciparum and P. vivax FISH assays [10], and the same considerations also apply to the PK-FISH assay. In essence, the FISH assays require no specialized equipment other than a light microscope with a LED source and filter attachments, and are less costly and simpler to perform than PCR-based tests.…”
Section: Discussionmentioning
confidence: 99%